Asymptomatic and early pseudoaneurysm of posterior superior pancreaticoduodenal artery and right gastric artery complicating acute pancreatitis: A case report - Occhionorelli, Savino (Int J Surg Case Rep, 2016)
INTRODUCTION: Arterial pseudoaneurysm is a rare and life-threatening complication of pancreatitis, seen more often in chronic than in acute pancreatitis. It involves mostly the splenic artery, while only in 10% of the case it appears in pancreaticoduodenal and gastric artery. This case report described an asymptomatic pseudoaneurysm of the posterior superior pancreaticoduodenal artery and of the right gastric artery, which occurred after 13 days from the episode of acute pancreatitis and, then it was treated with vascular angioembolization. PRESENTATION OF CASE: A 71 year-old female was admitted to the Emergency Surgery Department for severe acute pancreatitis. After 13 days from the onset, pseudoaneurysms were detected with a control contrast-enhanced computed tomography and they were localized in a branch of the right gastric artery and in a branch of the posterior superior pancreaticoduodenal artery. The patient underwent angiography and the pseudoaneurysms were treated with platinum coil embolization, without complications or further bleeding. DISCUSSION: This is an unusual case because of the low incidence of arterial pseudoaneurysm as acute pancreatitis complication (1.3–10%), and the uncommon localization in the pancreaticoduodenal arteries. CONCLUSION: It is important to be aware of pancreatitis-related arterial pseudoaneurysms, as they have a mortality of 90% if not recognized and treated, not only in chronic but also in acute pancreatitis, and to work out a scheduled follow-up with abdominal computed tomography or pancreatic contrast-enhanced ultrasound in order to control and prevent late onset complications.